The level of functional dependency and independency among the elderly people of old care homes in Bangladesh (Bangladesh Journal of Psychiatry, 2017)
The level of functional dependency of elderly is increasing day by day. The old care homes have been markedly increased in recent years in Bangladesh. The purpose of the study was to identify the level of functional dependency and independency among activities of daily living for the elderly people of old care homes in Bangladesh. A cross sectional study was conducted with a structured and close ended interviewer administered questionnaire to collect information from 144 elderly people of five old care homes through convenient sampling technique. The results showed that, 38 participants were fully functional (score 6), 56 participants had score 4 and they had moderate impairment, 40 participants score was 2 or less which indicated severe functional impairment and 10 participants were totally dependent (score 0). The study also revealed that 58% of the elderly people in the age group 60-65 years were independent and 70% of the elderly people belonging to age group >70 were totally dependent. However, it has been evident that percentage of independency decreases with the increase of age. It was also found that respondents at the age of 65 years and above were functionally dependent. This study also recommends for occupational therapy service in old care home.Bang J Psychiatry Dec 2014; 28(2): 62-66